Korupcja a sprzeczności klasowe w Chinach - Wiktor, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The corruption in China is not a new thing. But when the socialistic market economy has been implemented in China, there have arisen wide opportunities of bypassing or even breaking the law on politics-business junction. However, the corruption in the junction and especially in the mining industry is just a fragment of wider occurrence. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 349-358